Drugs, Denial, and Deflection: 1972, the Year New Zealand Sport Confronted Doping. Issue 12 (13th August 2019) - Hamilton, Bruce; Ryan, Greg
Abstract: Contemporaneously described as the unfortunate Games, the New Zealand team experience at the Munich Olympic Games was clouded by the Israeli hostage tragedy, and a series of controversies involving sex, amateurism and team mismanagement. However, the Munich Games also took place against an international background of overt political interference in sport and endemic drug use amongst athletes, juxtaposed with immature anti-doping systems. Using archival documents and contemporary sources, this paper briefly establishes the context for anabolic steroid use by athletes at the 1972 Olympic Games, prior to examining the allegations of anabolic steroid use by members of the New Zealand team. The subsequent response of the New Zealand Olympic and British Commonwealth Games Association and specific national sporting organizations to those allegations are highlighted and evaluated.